Long-term subjective loneliness in adults after hearing loss treatment. (3rd August 2019) - Applebaum, Jeremy; Hoyer, Matthew; Betz, Joshua; Lin, Frank R.; Goman, Adele M.
Abstract: Objective: While hearing loss is associated with loneliness, the long term impact of hearing loss interventions remains unknown. We investigated levels of loneliness in adults at baseline, 6-months, 1-year and 5-years after receiving a hearing aid (HA) or cochlear implant (CI). Design: In this 5-year follow-up to the Studying Multiple Outcomes after Aural Rehabilitative Treatment study, participants completed the University of California, Los Angeles (UCLA) Loneliness Scale at baseline, 6-months, 1-year, and 5-year time points. Generalized estimating equations modeled the population average UCLA score over time. Study Sample: Analytic cohort of 115 participants (74% of original 156) 50 years or older who received a HA or CI at baseline and completed at least one follow up visit. Results: Loneliness scores were not different at 5 years versus baseline for HA users. CI users showed significantly reduced loneliness at 6-months and 1-year from baseline and with no significant difference at 5 years. Conclusion: Over 5 years, we observed no increase in loneliness from baseline in a cohort of adults receiving HAs and CIs. Short-term reduction in loneliness in CI users was demonstrated. Future randomized trials are needed to definitively assess the impact of treated versus untreated hearing loss on loneliness.